The natural history of epilepsy: an epidemiological view. Issue 10 (16th September 2004) - Kwan, P; Sander, J W
Abstract : Better information of the natural history of epilepsy has important implications for understanding the underlying neurobiology, evaluating treatment strategies, and planning healthcare resources. The traditional pessimistic view has been dispelled by results from modern community based prospective studies, showing that over 60% of newly diagnosed patients will enter remission upon treatment. Recent outcome studies suggest that medical intractability may be predicted after failure of two antiepileptic drugs. Poor prognostic factors include a high initial seizure density, symptomatic aetiology, and presence of structural cerebral abnormalities, all of which can be identified early on. Among patients who have entered remission, many will remain seizure-free after antiepileptic drug treatment is withdrawn, suggesting that the underlying seizure generating factor has remitted. Whether some of these patients have entered remission "spontaneously" is contentious because, with effective pharmacotherapy for epilepsy in use for over 100 years, the natural history of untreated epilepsy is largely unknown. Circumstantial evidence, mostly arising from resource poor countries where antiepileptic drug treatment is not readily available, indicates that spontaneous remission may occur in up to 30% of cases. Observations from these complementary sources suggest that, at the population level, prognosis of newly diagnosed epilepsy may be broadly categorised into three groups: remission without treatment, remission with treatment only, and persistent seizures despite treatment. As understanding of the prognostic factors improves, the potential of a "prognostic group specific" management approach should be explored so that effective treatments may be used in a more rational and targeted fashion.